Dynamics of mtDNA introgression during species range expansion: insights from an experimental longitudinal study - Mastrantonio, V. (Sci Rep, 2016)
Introgressive hybridization represents one of the long-lasting debated genetic consequences of species range expansion. Mitochondrial DNA has been shown to heavily introgress between interbreeding animal species that meet in new sympatric areas and, often, asymmetric introgression from local to the colonizing populations has been observed. Disentangling among the evolutionary and ecological processes that might shape this pattern remains difficult, because they continuously act across time and space. In this context, long-term studies can be of paramount importance. Here, we investigated the dynamics of mitochondrial introgression between two mosquito species (Aedes mariae and Ae. zammitii ) during a colonization event that started in 1986 after a translocation experiment. By analyzing 1,659 individuals across 25 years, we showed that introgression occurred earlier and at a higher frequency in the introduced than in the local species, showing a pattern of asymmetric introgression. Throughout time, introgression increased slowly in the local species, becoming reciprocal at most sites. The rare opportunity to investigate the pattern of introgression across time during a range expansion along with the characteristics of our study-system allowed us to support a role of demographic dynamics in determining the observed introgression pattern.